Bilateral Simultaneous Middle Cerebral Artery Mechanical Thrombectomy for Periprocedural Transcatheter Aortic Valve Implantation Stroke: A Case Report - Govindappa, Sharath Kumar Goddu; M., Jayranganath; Jose, John; M., Somashekar C; Adiga, Chaitra Parameshwara (Journal of Clinical Interventional Radiology ISVIR, 2022)
Mechanical thrombectomy has been described as the prompt procedure for emergent large vessel occlusion strokes resulting from cardioembolic events, arterial lesion-to-artery embolism, or from in situ atherosclerosis. This is the first reported case of an elderly woman who presented with bilateral paresis, progressive drowsiness, and dysarthria due to bilateral middle cerebral arterial occlusion, originating from the aortic valve, after transcatheter aortic valve implantation, leading to stroke. Despite intravenous thrombolysis being begun for this patient, it proved ineffective and she underwent mechanical thrombectomy, which led to complete revascularization of bilateral middle cerebral arteries following which she completely recovered without any deficits.
Keywords: mechanical thrombectomy; TAVI; acute ischemic stroke